Analisa Literasi Keuangan pada Usaha Mikro Kecil Dan Menengah (UMKM) Batik di Kota Jambi - Ahmad Nur Budi Utama; Ade Irma Suryani (Universitas Batanghari, 2023)
The purpose of this study is to find out how experienced Batik micro, small and medium enterprises (MSMEs) in Jambi City are in financial matters. Data collection techniques through conversations or interviews with informants representing small and medium enterprises, and interviews conducted face-to-face. The aspects of financial literacy studied are: 1) Aspects of financial knowledge; (2) Aspects of financial behavior; 3) Aspects of financial attitudes; and 4) Aspects of financial capability. The results showed that (1) The aspect of financial knowledge shows that Batik MSME actors in Jambi City are able to use supporting devices, and financial products and make financial reports to support their business; (2) The aspect of financial behavior shows that Batik MSME actors in Jambi City are aware of paying taxes, setting aside money for savings, and recording finances accurately; (3) The aspect of financial attitude shows that Batik MSME actors in Jambi City are able to manage expenses rationally; and (4) The financial capabilityÂ aspect shows that Batik MSME players in Jambi City are able to have strategies and plans for where and how money will be spent and track savings balances.